Median nerve stimulation elevates ventricular fibrillation threshold via the cholinergic anti-inflammatory pathway in myocardial infarction canine model - Wang, Xuewen; Qian, Yongsheng; Yao, Yajun; Wang, Youcheng; Zhang, Youjing; Zhang, Shujuan; Zhao, Qingyan (Frontiers in Cardiovascular Medicine, 2022)
Background Median nerve stimulation (MNS) diminishes regional myocardial ischemia and ventricular arrhythmia; however, the underlying mechanism has not been elucidated. Methods In this study, we randomly categorized 22 adult mongrel dogs into a control group, MNS group 1, and MNS group 2. After a 4-week experimental myocardial infarction (MI), ventricular electrophysiology was measured in the MNS group 1 before and after 30 min of MNS. The same measurements were performed in the MNS group 2 dogs via bilateral vagotomy. Venous blood and ventricular tissue were collected to detect molecular indicators related to inflammation and cholinergic pathways by enzyme-linked immunosorbent assay (ELISA), immunohistochemistry (IHC), and Western blot (WB). Results No significant changes were reported in the ventricular effective refractory period (ERP) in the MNS group 1 and MNS group 2 dogs before and after MNS. The ventricular fibrillation threshold (VFT) in the MNS group 1 was significantly higher than that in the MNS group 2 (20.3 ± 3.7 V vs. 8.7 ± 2.9 V, P < 0.01). The levels of tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and nuclear transcription factor-κB (NF-κB) were lower (P < 0.01), whereas the levels of Ach were higher in the peri-infarct zone tissues in the MNS group 1 dogs than those in the MNS group 2 dogs (P < 0.01). Conclusion This study demonstrated that MNS increases VFT in a canine model with MI. The effects of MNS on VFT are potentially associated with the cholinergic anti-inflammatory pathway.